PELATIHAN PEMBUATAN LILIN AROMATERAPI UNTUK MENINGKATKAN KREATIVITAS REMAJA - Wardah Fauziyah Utami; Rinda Siaga Pangestuti; Tri Elsa Susilawati (An-Nizam, 2022)
This paper explores youth creativity through training in making aromatherapy candles. This training intends to empower the community in the midst of a pandemic where many people work from home and school children learn online. Conditions like this lead to stress, which can hinder work and remote learning. In particular, the stages of activities carried out in this training are socialization and practice of making aromatherapy candles. The participants who took part were teenagers around RT 003 in Kranji Bekasi Barat, and it was held in February 2022. This activity uses the science and technology diffusion method which produces an aromatherapy candle product. The results obtained in this training are that teenagers can increase their knowledge and practice how to make aromatherapy candle crafts using materials that are easy to find around. The hope from this activity is that teenagers are active and creative in utilizing existing materials to be turned into valuable materials.